When Do Mediators Say "No"? The Case of American Resistance to Mediating the Gulf Diplomatic Crisis. Issue 2 (15th April 2022) - Vuković, Siniša; Martin, Danielle
Abstract : When do mediators say "no" and refuse to manage an escalating conflict, even if they meet all of the prerequisites for jumpstarting a peacemaking process? Empirical studies to date have focused primarily on factors that facilitate the start of mediation efforts. Surprisingly, very little is known about the reasons that motivate third parties' refusal to engage. Working against the backdrop of conceptual frameworks that indicate when mediators say "yes, " this article offers a novel framework for analysis that explicates three conditions that dissuade third parties from mediating. Using the case of the U.S. resistance to mediate the Gulf diplomatic crisis, the article shows that mediators will refuse to mediate conflicts that are characterized by high levels of power symmetry, pronounced structural linkage with conflicting parties, and extensive strategic interests in the conflict‐affected area.